Reversible cerebral vasoconstriction syndrome in a 35-year-old woman following hysterectomy and bilateral salpingo-oophorectomy. (8th December 2011) - Moussavi, Mohammad; Korya, Daniel; Panezai, Spozhmy; Peeraully, Tasneem; Gizzi, Martin; Kirmani, Jawad F
Abstract : Introduction: Reversible cerebral vasoconstriction syndromes (RCVS) have been documented to take place after an inciting event or illness. They present with headache, altered mental status and focal neurologic findings. The differential diagnosis includes primary angiitis of the central nervous system (PACNS) but one major clinical difference is that the symptoms of RCVS usually resolve within days or weeks whereas PACNS is often fatal. Females of childbearing age are most commonly affected with RCVS. Cases of reversible vasculopathy have also been reported in menopausal women. The hormonal and physiologic changes that take place during the postpartum period and menopause may not be very different from those that occur after a hysterectomy and oophorectomy. Methods: A case is presented of a 35-year-old woman who underwent a hysterectomy with bilateral salpingo-oophorectomy and then began experiencing severe headaches, visual changes and hemi-sensory loss. Physical examination, imaging and laboratory findings were descriptive of RCVS, and the patient's rapid recovery was consistent with the usual disease progression of a reversible vasculopathy. Conclusion: A reversible cerebral vasoconstriction syndrome may occur in some circumstances after a hysterectomy with bilateral salpingo-oophorectomy. The mechanisms involved in the development of this condition are explained by current research concerning effects on the vasculature of sudden drops in estrogens and progesterones. More studies are required to further establish the pathophysiology, diagnosis and treatment of this condition.